Interdisciplinary communication in pianists’ education: experience from M. Hlinka Dnipropetrovsk academy of music - Lysenko, Yanina; Korotenko, Dariia; Martynyuk, Tetyana; Tkachenko, Olena; Vlasenko, Eleonora (Linguistics and Culture Review, 2021)
In modern social conditions, the demand of formation of a new generation of teachers is raising. The problem of interdisciplinary communication in the field of musical-pedagogical preparation of specialists is of particular interest since new organizational and methodological forms, theoretical and practical research are not used enough in the educational process. The authors conducted a study on the issues of professional and conceptual foundations of pianists’ education on the example of M. Hlinka Dnipropetrovsk Academy of Music. The concept of interdisciplinary communication was defined. Vocational and pedagogical skills and pianist skills that are formed due to the interconnection of the disciplines of the historical-pedagogical cycle were characterized. The tasks that contribute to ensuring the effectiveness of the results of pianists’ educational process in M. Hlinka Dnipropetrovsk Academy of Music were identified and main pedagogical principles were outlined.